A Multidimensional Evaluation-Based Reinterpretation of the Cultural Heritage Value of Blue-and-White Porcelain Patterns in Contemporary Design - Jiajia Zhao; Qian Bao; Ziyang Huang; Ru Zhang (Heritage)
Blue-and-white porcelain patterns embody rich symbolic meanings and play a pivotal role in the transmission of Chinese intangible cultural heritage. However, their contemporary application often faces challenges due to complex visual forms and contextual interpretations. This study adopts a semiotic perspective to reinterpret blue-and-white porcelain motifs as cultural heritage symbols, aiming to assess their potential for sustainable preservation and modern revitalization. A hybrid evaluation framework is proposed, combining Grey System Theory and the Fuzzy Evaluation Method to quantitatively analyze 40 representative patterns across five key dimensions: cultural symbolism, esthetic value, communicative potential, modern applicability, and sustainability. Data were collected from expert panels, public surveys, and market performance, with the Analytic Hierarchy Process (AHP) employed to determine the relative importance of each dimension. The results reveal that plant and geometric patterns exhibit high adaptability and symbolic clarity, making them ideal for reinterpretation in modern design. Conversely, complex narrative and animal-based motifs demonstrate weaker performance in communicative efficiency and sustainability, indicating the need for visual simplification and semantic transformation. This study provides a theoretical and methodological foundation for the revitalization of traditional porcelain heritage in contemporary design practice, contributing to the global dissemination and sustainable development of cultural heritage symbols.